SIGNIFIKANSI UJI KOMPETENSI AWAL TERHADAP KOMPETENSI PEDAGOGIK GURU KELAS MADRASAH IBTIDAIYAH DI KABUPATEN KUDUS TAHUN 2014 - Santoso, Nika Lucky; Ismanto, Ismanto (Pascasarjana IAIN Kudus, 2015)
This study aimed to describe: (1) The initial test of competence and pedagogical competence of MI teacher at Kudus district in 2014, and (2) the effect of the initial competency test against MI classroom teachers pedagogical competence in Kudus district in 2014. This research includes the study of ex post facto of correlational research. The samples using random sampling, with a standard error of 5% of the total population 130 MI classroom teachers at Kudusdistrict, obtained a sample of 98 people. The technique of collecting data through documentation and interviews with the LPTK Rayon 206 UIN Walisongo Semarang. While the analysis is done by using descriptive analysis and simple linear regression-correlation. The results showed that: (1) The initial test of competence and pedagogical competence of MI teacher at Kudus District 2014in the category good enough maing at 55.78 and 81.09 respectively, and (2) the initial competency test does not significantly influence the competence pedagogic of MI classroom teachers, with the model: Y = 78.047 + 0.056 X. While the initial competency test relations with pedagogical competence is positive and not significant with a correlation coefficient of 0.167 categorized as very low, so the initial competency test only contributes 2.8% of the MI teacher pedagogical competence in Kudus district.Penelitian ini bertujuan untuk mendeskripsikan: (1) uji kompetensi awal dan kompetensi pedagogik guru kelas Mi di kabupaten kudus tahun 2014, serta (2) pengaruh uji kompetensi awal terhadap kompetensipedagogik guru kelas Mi di kabupaten kudus tahun 2014. Penelitian ini termasuk jenis penelitian ex post facto bentuk correlational research. Penentuan sampel menggunakan random sampling, dengan taraf kesalahan 5% dari jumlah populasi 130 guru kelas Mi dari kabupaten kudus, didapatkan sampel sebanyak 98 orang. Teknik pengumpulan data melalui dokumentasi dan wawancara dengan pihak lPTk Rayon 206 UIN Walisongo Semarang. Sedangkan analisis yang dilakukan dengan menggunakan analisis deskriptif dan regresi-korelasi linier sederhana. hasil penelitian menunjukkan bahwa: (1) uji kompetensi awal dan kompetensi pedagogik guru kelas Mi di kabupaten kudustahun 2014 dalam kategori cukup baik maing-masing sebesar 55,78 dan 81,09, serta (2) uji kompetensi awal tidak berpengaruh signifikan terhadap kompetensi pedagogik guru kelas Mi, dengan model:Ŷ = 78,047 + 0,056 X. Sedangkan hubungan uji kompetensi awal dengan kompetensi pedagogik adalah positif dan tidak signifikan dengan koefisienkorelasi sebesar 0,167 berkategori sangat rendah, sehingga uji kompetensi awal hanya memberikan kontribusi sebesar 2,8% terhadap kompetensi pedagogik guru kelas madrasah ibtidaiyah di kabupaten kudus.